STEM-Based Physics Modules with CK-12 Simulations for High School Students: Development and Implementation - Nurlina, Nurlina; M., Musdar; Hajati, Kartika; Zulfiani, Ulfa (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2024)
Research has been conducted to develop STEM-based physics modules with CK-12 simulations for high school students. This study evaluates the STEM-based physics module’s validity, practicality, and effectiveness with CK-12 simulations for grade X students. The research employed research and development (R&D), utilizing the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The study involved three expert validators and students from two schools to assess the module’s validity, practicality, and effectiveness. The participants comprised grades X MIA students from SMAN 1 Alu and X IPA students from MAN 2 Polewali Mandar. The validity of the developed physics modules, presented as a practical module, was assessed through expert validation, while practicality was evaluated using response questionnaires completed by students and teachers. Effectiveness was determined based on student learning outcome tests. The results indicate that the physics module was highly valid, with an overall validity score of 87.78%. Practicality was also rated highly, with scores of 90.29% from students and 99.00% from teachers. Furthermore, the module demonstrated effectiveness, as evidenced by student learning outcomes meeting the established criteria, with an effectiveness score of 79.17%. These findings suggest that STEM-based physics modules with CK-12 simulations can significantly enhance the quality of physics teaching and learning for high school students. In addition, this research should be explored for other topics.